Opportunity structures in vocational education and training : national studies and international discussions - Smeplass, Eli [Herausgeber]; Zirkle, Chris [Herausgeber] (Palgrave Macmilian, 2026)
This book unites authors from diverse societal contexts and academic disciplines to promote a positive discourse around vocational education and training (VET). VET specialists from different national contexts present positive structures that enable participation, freedom, practical learning and provide hope and engagement. Throughout the book, the term 'opportunity structures' is used to illustrate these concepts. Split into two parts, chapters first focus on evidence-based contributions before moving on to conceptual discussions. Overall, the book argues that VET pathways play a pivotal role in providing opportunities for young and adult learners globally. The book will be of interest to academics, researchers and educators in the field of VET and related fields, such as teacher training, comparative education, adult education and workforce development." (Publisher, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; I 2.2.1 Westeuropa; I 2.3.1 Afrika; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; I 2.3.4 Asien; 370; Berufsausbildung; Berufliche Weiterbildung; Erwachsenenbildung; Lebenslanges Lernen; Berufsbildungssystem; Bildungschance; Vergleichende Berufsbildungsforschung; Bundesrepublik Deutschland; Costa Rica; Finnland; Norwegen; Österreich; Simbabwe; Spanien; Südkorea; USA